2020
DOI: 10.1093/jrr/rrz082
|View full text |Cite
|
Sign up to set email alerts
|

Inter-unit variability of multi-leaf collimator parameters for IMRT and VMAT treatment planning: a multi-institutional survey

Abstract: Modern treatment machines have shown small inter-unit variability regarding beam data. Recently, vendor-provided average beam data, such as the Representative Beam Data (RBD) of the TrueBeam (Varian Medical Systems, Palo Alto, CA, USA), has been used for modeling of the Eclipse (Varian Medical Systems) treatment planning system. However, RBD does not provide multi-leaf collimator (MLC) parameters, such as MLC leaf transmission factor (LTF) and dosimetric leaf gap (DLG). We performed a web-based multi-instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Glenn et al reported institutional variation up to ±25% from the mean value of the TF and DLG for Varian linacs and the Eclipse TPS 3 . Isono et al showed that the variations in the measured DLG were up to ±18% from the mean value for the Varian TrueBeam with the Millennium 120 MLC 4 . For example, for a IMRT plan we examined in this study, the maximal change in dose profile was about 7% in the area of high dose gradient for the 25% change of the DLG, and the maximal change was about 7% in the area just outside of the field edge formed by MLCs for the 25% change of the TF.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glenn et al reported institutional variation up to ±25% from the mean value of the TF and DLG for Varian linacs and the Eclipse TPS 3 . Isono et al showed that the variations in the measured DLG were up to ±18% from the mean value for the Varian TrueBeam with the Millennium 120 MLC 4 . For example, for a IMRT plan we examined in this study, the maximal change in dose profile was about 7% in the area of high dose gradient for the 25% change of the DLG, and the maximal change was about 7% in the area just outside of the field edge formed by MLCs for the 25% change of the TF.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of MLC modeling and the detectability of its errors at each institution have recently been questioned from various viewpoints. Some institutional surveys revealed that MLC modeling parameters such as the TF and DLG showed considerable variation even among the same types of linacs and TPSs 3,4 . Glenn et al reported institutional variation up to ±25% from the mean value of the TF and DLG for Varian linacs and the Eclipse TPS 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern day radiotherapy frequently utilizes modulated treatment, either in form of static gantry dynamic multileaf collimator (MLC) treatments or volumetric modulated treatment (VMAT), 1 for which the gantry, MLC leaves, and dose rate constantly change during beam delivery 2 . Such advanced treatment techniques require a well‐controlled beam delivery during all stages of treatment, a stable beam, and a robust MLC model implemented in the treatment planning system (TPS), especially when consideration is given to reduction of standard planning target volume (PTV) margins in stereotactic body radiotherapy (SBRT) 3 …”
Section: Introductionmentioning
confidence: 99%
“…QA tools (16). As the number of verification plans and parameters increases, the necessity to establish suitable and common MLC parameters increases accordingly.…”
mentioning
confidence: 99%